Pendaftaran Peralihan Hak Atas Tanah Berdasarkan Akta Pengikatan Perjanjian Jual Beli di Kota Padang - Elittrosint, Vicia (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2020)
Each Land Office has a different policy in accepting return registration of certificates based on PPJB, some accept and some reject. Based on this description, the author is interested in discussing this thesis with the title